2013
DOI: 10.1039/c3cs60205b
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature plasma synthesis of carbon nanotubes and graphene based materials and their fuel cell applications

Abstract: Carbon nanotubes (CNTs) and graphene, and materials based on these, are largely used in multidisciplinary fields. Many techniques have been put forward to synthesize them. Among all kinds of approaches, the low-temperature plasma approach is widely used due to its numerous advantages, such as highly distributed active species, reduced energy requirements, enhanced catalyst activation, shortened operation time and decreased environmental pollution. This tutorial review focuses on the recent development of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(84 citation statements)
references
References 53 publications
0
84
0
Order By: Relevance
“…51 The PECVD has also been successfully implemented to dope CNT and graphene. 55,56 Plasma based techniques have been predominantly applied to the initial synthesis of carbon-based materials rather than post processing. Plasma also has considerable potential for post synthesis functionalization of carbon based materials.…”
Section: Plasma In Carbon Nanotechnologymentioning
confidence: 99%
“…51 The PECVD has also been successfully implemented to dope CNT and graphene. 55,56 Plasma based techniques have been predominantly applied to the initial synthesis of carbon-based materials rather than post processing. Plasma also has considerable potential for post synthesis functionalization of carbon based materials.…”
Section: Plasma In Carbon Nanotechnologymentioning
confidence: 99%
“…However, the low adsorption capacity and/or slow adsorption rate of these adsorbents limits the potential application in environmental cleanup. It is demonstrated that graphene oxides (GOs) exhibited larger adsorption capacities for heavy metals than commercial granular active carbon and carbon nanotubes because of their large surface area, a variety of oxygen-containing functional groups, and numerous reactive sites on the surface of nanosheets [15][16][17][18][19][20][21][22]. Plenty of studies on the adsorption of Cd(II) on graphene oxides were available in recent years [23][24][25][26][27][28], whereas the interaction mechanism between Cd(II) and oxygencontaining functional groups of GOs by surface complexation modeling were still scarcely.…”
Section: Introductionmentioning
confidence: 99%
“…3. In the FTIR spectrum of graphene oxides, various oxygenated functional groups, such as C-OH (broad peak at~3400 cm −1 ), −COOH group (at~1700 cm −1 ), C_O group (at~1400 cm −1 ) and C-O-C group (at~1050 cm −1 ) were found on graphene oxide surfaces [27,29]. The strong peak at~3400 cm −1 was attributed to the stretching vibration of the -OH groups associated with the layered structure of titanate and graphene oxides [14,15].…”
Section: Characterizationmentioning
confidence: 99%